2020
DOI: 10.34208/jba.v22i1.628
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Corporate Social Responsibility Reporting Terhadap Manajemen Laba

Abstract: Tujuan penelitian ini adalah untuk menguji apakah pengungkapan CSR (Corporate Social Disclosure) berpengaruh terhadap manajemen laba yang dilakukan oleh manajemen perusahaan. Manajemen laba diukur dengan menentukan besarnya manajemen laba akrual yang dilakukan oleh perusahaan dengan menghitung nilai discretionary accrual dan untuk pengungkapan CSR menggunakan index GRI (Global Reporting Initiative). Sampel penelitian ini menggunakan perusahaan manufaktur yang terdaftar pada Bursa Efek Indonesia (BEI) selama ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
2
3
1
7
Order By: Relevance
“…In addition, from several aspects contained in the Global Reporting Initiative reporting guidelines, it was found that several aspects of the quality of environmental accounting disclosures disclosed by companies, such as aspects of energy, emissions, waste and biodiversity, still showed low quality. This result is in line with the findings of (Alexander & Palupi, 2020) states that the implementation carried out by the company is less firm regarding the implementation that must have an impact on decreasing the quality of environmental performance and the impact on discretionary accruals. These findings are in agreement with (Alexander & Palupi, 2020) explains the quality of environmental accounting disclosures affects the level of discretionary accruals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, from several aspects contained in the Global Reporting Initiative reporting guidelines, it was found that several aspects of the quality of environmental accounting disclosures disclosed by companies, such as aspects of energy, emissions, waste and biodiversity, still showed low quality. This result is in line with the findings of (Alexander & Palupi, 2020) states that the implementation carried out by the company is less firm regarding the implementation that must have an impact on decreasing the quality of environmental performance and the impact on discretionary accruals. These findings are in agreement with (Alexander & Palupi, 2020) explains the quality of environmental accounting disclosures affects the level of discretionary accruals.…”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with the findings of (Alexander & Palupi, 2020) states that the implementation carried out by the company is less firm regarding the implementation that must have an impact on decreasing the quality of environmental performance and the impact on discretionary accruals. These findings are in agreement with (Alexander & Palupi, 2020) explains the quality of environmental accounting disclosures affects the level of discretionary accruals. Social responsibility reports can reduce earnings management practices because the information provided to stakeholders is more a form of corporate responsibility to stakeholders so that this information will reduce earnings management practices in the company.…”
Section: Discussionsupporting
confidence: 90%
“…Penelitian ini bertujuan untuk menguji pengaruh kesadaran moral dan pengawasan atas laporan keuangan terhadap manajemen laba. Penelitian sebelumnya telah meneliti mengenai pengaruh kualitas auditor terhadap manajemen laba (Mela, 2019;Yasser & Soliman, 2018) dan pengaruh pengungkapan tanggung jawab sosial terhadap manajemen laba (Alexander & Palupi, 2020;Pakawaru et al, 2021). Namun belum ada penelitian yang meneliti pengaruh tanggung jawab sosial dan kualitas auditor apabila perusahaan memiliki keduanya.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini konsisten dengan penelitian Rahmawardani & Muslichah (2020), Kinasih et al (2018) yang menunjukkan bahwa corporate social responsibility berpengaruh negatif dan signifikan terhadap manajemen laba. Hasil penelitian Alexander & Palupi (2020) juga menjelaskan bahwa corporate social responsibility dapat mengurangi praktik manajemen laba karena semakin transparannya informasi yang diberikan oleh perusahaan kepada pemangku kepentingan.…”
Section: Populasi Dan Sampelunclassified